Fractional radiofrequency combined with sonophoresis to facilitate skin penetration of 5-aminolevulinic acid. Issue 1 (January 2016) - Park, Jong; Jeong, Ki-Heon; Bae, Myong; Lee, Sang-Jun; Kim, Nack-In; Shin, Min
Abstract Ablative fractional technology has been used to improve transdermal drug delivery. However, there have been few previous in vivo investigations of the relative potency and methodology of fractional radiofrequency (RF) combined with sonophoresis. The purpose of this study was to investigate the effects of fractional RF combined with sonophoresis on 5-aminolevulinic acid (ALA) penetration of the skin. Three male domestic swine were used. The skin of the pigs was exposed to fractional RF and/or sonophoresis, followed by topical ALA application. Fluorescence intensity (FI) of porphyrin fluorescence was measured. In both the epidermis and the dermis, FI increased after fractional RF and increased additionally with the addition of sonophoresis. Fractional RF with sonophoresis effectively enhanced ALA skin penetration. Pre-fractional RF followed by posttreatment with sonophoresis can be used for ALA-photodynamic therapy to achieve higher ALA uptake.